Delivering User-Centric Climate Agro- Advisories to Smallholder Farmers in Ethiopia - Tesfaye, Kindie; Walelign, Hiwot; Endrias, Abrhame; Makonnen, Brook T. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
A strong public-private partnership enabled the delivery of tailored climate agro-advisories to smallholder women and men farmers in Ethiopia.